ESTIMASI KERUGIAN EKONOMI AKIBAT GIZI BURUK PADA BALITA DI BERBAGAI KABUPATEN/KOTA DI LUAR PULAU JAWA DAN BALI - Indah Yuliana; Drajat Martianto; Sri Anna Marliyati (ARGIPA (Arsip Gizi dan Pangan), 2017)
The purpose of this study was to estimate economic lost due to severe underweight amongunderfve children in various cities/regencies outside Java and Bali Islands. A bundle of secondarydata, namely: nutritional status of underfve children from 2007 Riskesdas, demographic data,GDRP (Gross Domestic Regional Product), and poverty level are gathered and analyzed toelaborate the study objectives. All of 314 cities/regencies at outside of Java and Bali Island weretreated as sample of this study. Data processing and analysis were conducted in Bogor, from Mayto July 2010. The study show that the higher poverty level, the higher the prevalence of severeunderweight. On the other hand, the higher the GDRP per capita the lower the prevalence ofsevere underweight. The study showed that economic lost due to severe among underfve childrenin outside Java and Bali Islands was ranged from 0,1% GDRP to 0,45% GDRP (r = 5%) andwas ranged from 0,11% GDRP to 0,51% GDRP (r = 10%). The highest economic lost due tosevere underweight was found in District of Mimika, Papua, and the lowest was Tomohon City,North Sulawesi.